Paediatric asthma and non‐allergic comorbidities: A review of current risk and proposed mechanisms. Issue 9 (28th July 2022) - Brew, Bronwyn K.; Osvald, Emma Caffrey; Gong, Tong; Hedman, Anna M.; Holmberg, Kirsten; Larsson, Henrik; Ludvigsson, Jonas F.; Mubanga, Mwenya; Smew, Awad I.; Almqvist, Catarina
Abstract: It is increasingly recognized that children with asthma are at a higher risk of other non‐allergic concurrent diseases than the non‐asthma population. A plethora of recent research has reported on these comorbidities and progress has been made in understanding the mechanisms for comorbidity. The goal of this review was to assess the most recent evidence (2016–2021) on the extent of common comorbidities (obesity, depression and anxiety, neurodevelopmental disorders, sleep disorders and autoimmune diseases) and the latest mechanistic research, highlighting knowledge gaps requiring further investigation. We found that the majority of recent studies from around the world demonstrate that children with asthma are at an increased risk of having at least one of the studied comorbidities. A range of potential mechanisms were identified including common early life risk factors, common genetic factors, causal relationships, asthma medication and embryologic origins. Studies varied in their selection of population, asthma definition and outcome definitions. Next, steps in future studies should include using objective measures of asthma, such as lung function and immunological data, as well as investigating asthma phenotypes and endotypes. Larger complex genetic analyses are needed, including genome‐wide association studies, gene expression–functional as well as pathway analyses or Mendelian randomization techniques; and identification of gene–environment interactions, such as epi‐genetic studies or twin analyses, including omics and early life exposure data. Importantly, research should have relevance to clinical and public health translation including clinical practice, asthma management guidelines and intervention studies aimed at reducing comorbidities. Abstract : We conducted a review of recent research regarding the comorbidity of asthma and non‐allergic diseases in children. There is increasing evidence for a number of co‐morbidites with a range of possible mechanisms including common genetic factors, early life risk factors and causal associations.